(untitled) (Global Journal of Human-Social Science, 2017)
Through observation of students behaviour foreign language teachers often seek ways to improve their teaching of a foreign language Teachers teaching of a foreign language observe their students behaviours analyze them identify possible problems propose intervention for the problem and evaluate the results after implementation of the proposed intervention Some solutions succeed others fail When this approach results in a self-reflective spiral of planning acting observing reflecting and re-planning it is called Action Research Mc Niff Whitehead 2002 46 It is a practical approach which aims to develop the process of teaching and learning by empowering participants and extending participation through collaboration Zuber-Skerritt 1991 2 In this paper I will show how Action Research succeed to solve a problem that I have faced in my familiar classroom According to the Action Research approach solving problems of teaching that may happen in TESOL classrooms takes collaboration and much participation Each teacher should play a great and essential role as a collaborator to help students to improve both teaching and learning levels In addition it is important for a teacher to evaluate any proposed solution through assessing the level of the students In fact the levels of the students partly reflect the level of the teacher and her his effort in developing the procession of education School and teachers can be considered two essential factors of the factors of students success Where Fullen 2001 115 argues that educational change depends on what teachers do and think it is as simple and as complex as that Willis reminds us that individual human action is embedded in cultural and structural systems not of the individual s making Willis 1977 Herein lies the value of Action Research for TESOL as a collective selfreflective inquiry undertaken by participants in social situations in order to improve the rationality and justice of th